Implementation of Management in Improving the Quality of Education in Al Ittifaqiah Indralaya Islamic Kindergarten - Rahmawati, Eka (Journal of Social Work and Science Education, 2023)
This study aims to describe how the implementation of management in improving the quality of education in the Al Itifaqiah Indralaya Islamic Kindergarten. This research was conducted at the South Sumatra High School located in Jakabaring, Palembang, South Sumatra. This research was conducted at the Al Ittifaqiah Islamic Kindergarten, Indralaya District, Ogan Ilir Regency. The time for carrying out the research was carried out for six months, from August to December 2022. The research is a type of qualitative research with an analytical descriptive flow which has the aim of proving various kinds of norms and theories regarding the quality of education in terms of improving the quality of education and its application to objects study. In qualitative research, the information obtained is generally in the form of words, descriptive, and the majority is not in the form of numbers. Collecting data and information obtained by researchers while in the field by obtaining direct surveys and documentation and research results show that improvements in various fields in education can improve the quality of education in Al Ittifaqiah Islamic Kindergarten.